Transparansi Pengelolaan Masjid dengan Laporan Keuangan Berdasarkan Pernyataan Standar Akuntansi Keuangan (PSAK 45) - Wiwin Kurniasari (IAIN Salatiga, 2011)
This article describes about the financial management of the mosque, which is one major factor in maintaining the survival and prosperity of the mosque. Good financial management of the mosque, also requires accurate financial reporting systems, especially relating to: 1) the circumstances and conditions of pilgrims, 2) the circumstances and financial condition of the property and the mosque and, 3) other information required in connection with the interests of the mosque. It aims to accountability to the board and the mosque. In order to apply the principle of openness (transparency) and accountability to the community, the management of an organizational entity in this public space mosques need to make corrections administration, including the publication of consolidated financial accountability. The growing demands on the implementation of accountability in this mosque, it will increase the need for transparency of financial information. This financial information serves as a basic consideration in the decision making process. Therefore we need the financial management of the mosque is based on the Statement of Financial Accounting Standards (PSAK) No. 45 requires accounting in organizations non-profit (in this case is a mosque) using the accrual method, which consists of statements of financial position, activity reports, cash flow statement and notes to the financial statements (IAI 2007).